2011
DOI: 10.1038/npp.2011.238
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Varenicline Treatment with Antipsychotic Medications for Cognitive Impairments in People with Schizophrenia: A Randomized Double-Blind Placebo-Controlled Trial

Abstract: The aim of this study is to examine the effects of treatment with varenicline, a partial agonist at the a4b2 and full agonist at the a7 nicotine acetylcholine receptor, on cognitive impairments in people with schizophrenia. In all, 120 clinically stable people with schizophrenia participated in randomized, double-blind, placebo-controlled 8-week trial. Antipsychotic and concomitant medication doses remained fixed throughout the study. Varenicline was titrated up to 1 mg twice daily for weeks 2-8. Neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 41 publications
5
66
0
Order By: Relevance
“…The literature suggests that both severity of positive and negative symptoms (Hughes et al, 2003) and longer durations of untreated psychoses (Amminger et al, 2002;Lappin et al, 2007) are linked to poorer cognitive performance in first episode psychosis. Effects of antipsychotic drugs on cognitive performance in patients with schizophrenia are not entirely clear: while some studies found positive effects (Selva-Vera et al, 2010;Shim et al, 2012) others found either no effects (Remillard et al, 2008;Kelly et al, 2009) or effects varying by type of medication (conventional/atypical) (Müller et al, 2005). Fourth, the individuals in our sample were all males.…”
Section: Discussionmentioning
confidence: 78%
“…The literature suggests that both severity of positive and negative symptoms (Hughes et al, 2003) and longer durations of untreated psychoses (Amminger et al, 2002;Lappin et al, 2007) are linked to poorer cognitive performance in first episode psychosis. Effects of antipsychotic drugs on cognitive performance in patients with schizophrenia are not entirely clear: while some studies found positive effects (Selva-Vera et al, 2010;Shim et al, 2012) others found either no effects (Remillard et al, 2008;Kelly et al, 2009) or effects varying by type of medication (conventional/atypical) (Müller et al, 2005). Fourth, the individuals in our sample were all males.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, the α4β2 nAChR agonist, AZD3480, is in Phase II clinical trials for Alzheimer's disease (http://clinicaltrials.gov/show/NCT01466088). The partial α4β2 nAChR agonist and full α7 nAChR agonist varenicline was shown to have a beneficial effects on cognition in patients with schizophrenia when used in addition to antipsychotic drug treatment (Shim et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Full-text assessments of the remaining 11 potentially relevant articles excluded a further three studies [37][38][39]. A total of eight studies (398 participants) met the selection criteria and were included in the analysis [40][41][42][43][44][45][46][47]. The included studies were published between 2011 and 2014.…”
Section: Included Studiesmentioning
confidence: 99%
“…Three studies explored the effectiveness of varenicline alone, and the remaining studies evaluated varenicline in combination with individual behavioural interventions [42, 44,47]. The duration of the varenicline treatment varied between eight and twelve weeks, and 81% of participants treated with varenicline completed the treatment, compared with 82% in placebo groups.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation